PERAWATAN PAYUDARA DALAM MENINGKATKAN PRODUKSI ASI PADA IBU NIFAS - Ratnasari, Febi; Melinda, Refy; Septian, Reza Rizki; Afifah, Risa; Agustina, Riska; Lestari, Rivka Dwi; Alfackri, Rizal; Sahpitri, Sahpitri; Lestari, Sari; Sartiyah, Sartiyah; Selamita, Selamita (Nusantara Hasana Berdikari, 2022)
Breast care is an action to care for the breasts, especially during the puerperium(breastfeeding period) to facilitate the release of breast milk. Breast care is caring for the breasts after the mother gives birth and breastfeeding which is a way to take care of the breasts so that milk comes out smoothly. Objective to increase knowledge about breast care in increasing milk production in postpartum mothers. Methods online counseling using power point presentations on the anatomy and physiology of lactation and breast care as well as demonstrations on how to do breast care for postpartum mothers through the Zoom Meeting application. There is an increase in knowledge and insight of mothers regarding breast care in increasing milk production in postpartum mothers.